At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find all the real zeros of the given polynomial and write the polynomial in factored form, let's break it down step-by-step.
We are given the polynomial:
[tex]\[ P(x) = x^4 - 2x^3 - 48x^2 + 98x - 49 \][/tex]
### Step 1: Find the Zeros
The zeros are the values of [tex]\( x \)[/tex] that make the polynomial equal to zero. According to our factorization:
[tex]\[ P(x) = (x - 7)(x - 1)^2(x + 7) \][/tex]
By setting each factor equal to zero and solving for [tex]\( x \)[/tex], we get the zeros of the polynomial. Let's solve it:
1. [tex]\((x - 7) = 0 \quad \Rightarrow \quad x = 7\)[/tex]
2. [tex]\((x - 1)^2 = 0 \quad \Rightarrow \quad x = 1\)[/tex] (Note: It's a double root because of the squared term)
3. [tex]\((x + 7) = 0 \quad \Rightarrow \quad x = -7\)[/tex]
So, the zeros of the polynomial [tex]\( P(x) \)[/tex] are [tex]\( x = 7 \)[/tex], [tex]\( x = 1 \)[/tex] (with multiplicity 2), and [tex]\( x = -7 \)[/tex].
### Step 2: Write the Polynomial in Factored Form
The factored form combines all the found zeros into the expression based on their multiplicities:
[tex]\[ P(x) = (x - 7)(x - 1)^2(x + 7) \][/tex]
### Summary
The real zeros of the polynomial [tex]\( P(x) = x^4 - 2x^3 - 48x^2 + 98x - 49 \)[/tex] are [tex]\( x = 7 \)[/tex], [tex]\( x = 1 \)[/tex] (with multiplicity 2), and [tex]\( x = -7 \)[/tex].
In factored form, the polynomial is:
[tex]\[ P(x) = (x - 7)(x - 1)^2(x + 7) \][/tex]
Thus, the final answer can be rewritten as follows:
[tex]\[ \boxed{ \begin{array}{l} \text{Zeros: } x = 7, \, x = 1 \, (\text{multiplicity 2}), \, x = -7 \\ \text{Factored Polynomial: } P(x) = (x - 7)(x - 1)^2(x + 7) \end{array} } \][/tex]
We are given the polynomial:
[tex]\[ P(x) = x^4 - 2x^3 - 48x^2 + 98x - 49 \][/tex]
### Step 1: Find the Zeros
The zeros are the values of [tex]\( x \)[/tex] that make the polynomial equal to zero. According to our factorization:
[tex]\[ P(x) = (x - 7)(x - 1)^2(x + 7) \][/tex]
By setting each factor equal to zero and solving for [tex]\( x \)[/tex], we get the zeros of the polynomial. Let's solve it:
1. [tex]\((x - 7) = 0 \quad \Rightarrow \quad x = 7\)[/tex]
2. [tex]\((x - 1)^2 = 0 \quad \Rightarrow \quad x = 1\)[/tex] (Note: It's a double root because of the squared term)
3. [tex]\((x + 7) = 0 \quad \Rightarrow \quad x = -7\)[/tex]
So, the zeros of the polynomial [tex]\( P(x) \)[/tex] are [tex]\( x = 7 \)[/tex], [tex]\( x = 1 \)[/tex] (with multiplicity 2), and [tex]\( x = -7 \)[/tex].
### Step 2: Write the Polynomial in Factored Form
The factored form combines all the found zeros into the expression based on their multiplicities:
[tex]\[ P(x) = (x - 7)(x - 1)^2(x + 7) \][/tex]
### Summary
The real zeros of the polynomial [tex]\( P(x) = x^4 - 2x^3 - 48x^2 + 98x - 49 \)[/tex] are [tex]\( x = 7 \)[/tex], [tex]\( x = 1 \)[/tex] (with multiplicity 2), and [tex]\( x = -7 \)[/tex].
In factored form, the polynomial is:
[tex]\[ P(x) = (x - 7)(x - 1)^2(x + 7) \][/tex]
Thus, the final answer can be rewritten as follows:
[tex]\[ \boxed{ \begin{array}{l} \text{Zeros: } x = 7, \, x = 1 \, (\text{multiplicity 2}), \, x = -7 \\ \text{Factored Polynomial: } P(x) = (x - 7)(x - 1)^2(x + 7) \end{array} } \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.